Analisis Kebutuhan Pengembangan Instrument Ilionis Agility Tes Berbasis Teknologi Di Ruang Lingkup FKIP Universitas Sriwijaya - Kurniawan, Eki Febri; Hartati, Hartati; Usra, Meirizal; Pranata, Doni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research is preliminary research to develop a tool that measures the agility ability of an athlete or student automatically and modern using a sensor system and application-based. This study is a survey research using unstructured questionnaires. Five statements have been prepared to find out how much the a need for the development of agility test instruments. The survey results show that most respondents have difficulty in using traditional measurement instruments, only a small percentage of respondents report using these instruments. All respondents involved in this survey agreed that agility test instruments can be developed and modernized from manual measuring instruments to fully automated measuring instruments. The results of this research will be used as a consideration for the development of an effective and easy-to-use scientific agility test instrument. Keywords: measuring instruments, agility, and modernization.